The Use of Instagram Reels „Täglicher “ Content in Konversation Course by German Language Education Students of Universitas Negeri Malang - Annida, Sharen; Bukhori, Herri Akhmad (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2023)
This research aims to explain the use of Instagram Reels „täglicher Vlog” content as a learning media in the Konversation course and to find out students’ responses to the use of this media. The method used in this research is descriptive qualitative with three stages of research procedures, namely pre-research, research, and post-research. The instruments used in this research are observation sheets and interview sheets. The data sources used in this research are 38 students from offering A and B 2021 of the German Language Education Study Program, Universitas Negeri Malang who took the Konversation course and are randomly selected as research samples. Data collection techniques in this research are observation and interview. The results of the research show that the use of Instagram Reels content „täglicher Vlog” obtain positive responses because students consider this media is easy to understand, could improve speaking skills, and provide motivation to learn German. In addition, the content of Instagram Reels „täglicher Vlog” which is interesting and educational can help their speaking skill in Konversation course. Students’ self-confidence also increases because the students are trained to learn expression through the „täglicher Vlog” Instagram Reels content.